Indonesia Economic Quarterly, December 2018 : Strengthening Competitiveness - World Bank (World Bank, Washington, DC, 2018)
After a challenging 10 months of capital outflows, currency depreciation, higher government bond yields and mounting pressures from fuel prices, November brought respite to Indonesia: global oil prices fell, and capital flows returned, leading to currency appreciation and lower bond yields. Nevertheless, the global and domestic dynamics that prevailed for the initial 10 months of 2018 remain mostly in place, and this edition of the Indonesian Economic Quarterly highlights the importance of structural reforms to increase exports and foreign direct investment, which will strengthen Indonesia’s external position.